Ensino de História e audiovisual : um roteiro para leitura de 1964 : o Brasil entre armas e livros - Nascimento, Reginaldo Lourenço do (2021)
This master‘s degree has, as a general theme, the revision of the historical negationismand the use of audiovisual products for the History teaching. The thesis aims at presenting a discussion whose objective is to indicate general aspects that help in the reading of audiovisual products. Thus, the proposal consists of the construction of a pedagogical material that can be used as a guide for the reading of audiovisual products displayed in a virtual platform. This material suggests the use of the documentary of the BrasilParalelo channel whose title is ―1964 – Brazil between guns and books” (2019). The civil-military coup of 1964 is the focus of the documentary. Documentary, as well as bibliographic research were carried out, and, posteriorly, a dissertation with tree chapters is intended to be presented. Such chapters aim at justifying the product constructed and entitled ―Audiovisual and History Teaching: a guide for the reading of 1964 – Brazil between guns and books.